Korelasi Sumber Hukum Islam Antara Al Qur’an, Hadits dan Ushul Fiqh - Mughni, M. Saefudin (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2020)
Islam is a religion that teaches compassion to all nature, because it has been equipped with a book of the Qur'an as a source of law, in which teaches about the intrinsic life, it is the word of God mandated to his Messenger to be conveyed to his people in order to complete the purpose of his life in the world and to achieve happiness in the eternal hereafter. With time travel, there are some things that can not be found solutions in the Holy Qur'an, therefore the scholars associate the source of Islamic law with other legal sources. This type of research is research library or library research, with documentation methods from various sources of literature. The results of this study showed that in addition to the legal source of the Qur'an is the hadith of the prophet Muhammad SAW, Ijma (the agreement of the scholars in determining the law due to different conditions) and Qiyas (liken a problem to the events contained in the Qur'an and hadith). The source of Islamic law in the form of Ijma and Qiyas must be based on the strong evidences of syar'i namely the Qur'an and al-Hadith, because as good as the guidelines or the handle of life of Muslims to be safe in the world and the hereafter is the holy book of the Qur'an and al-Hadith.